2019
DOI: 10.1002/bit.26963
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron transfer of different mediators for strictly opposite shifting of metabolism in Clostridium pasteurianum grown on glycerol in a new electrochemical bioreactor

Abstract: Microbial electrosynthesis or electro-fermentation in bioelectrochemical systems (BES) have recently received much attention. Here, we demonstrate with the glycerol metabolism by Clostridium pasteurianum that H 2 from in situ water electrolysis, especially in combination with a redox mediator, provides a simple and flexible way for shifting product selectivity and enhancing product yield in the fermentation process. In particular, we report and quantify for the first time strictly different effects of Neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 52 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…(B) 2,3-butanediol production in a hydrogenase-deficient S. oneidensis using native Mtr proteins and exogenous light-driven proton pump (proteorhodopsin) for NADH accumulation [52] . (C) Different effects of neutral red (NR) and the barely studied redox mediator brilliant blue (BB) on the growth and product formation of C. pasteurianum grown on glycerol in a newly developed bioelectrochemical system [54] . (D) Chiral alcohol (R)-1-phenylethanol production from acetophenone in engineered E. coli by using methyl viologen (MV) as mediator to achieve EET [55] .…”
Section: Microbial Electrosynthesis (Cathodic Electro-fermentation)mentioning
confidence: 99%
See 1 more Smart Citation
“…(B) 2,3-butanediol production in a hydrogenase-deficient S. oneidensis using native Mtr proteins and exogenous light-driven proton pump (proteorhodopsin) for NADH accumulation [52] . (C) Different effects of neutral red (NR) and the barely studied redox mediator brilliant blue (BB) on the growth and product formation of C. pasteurianum grown on glycerol in a newly developed bioelectrochemical system [54] . (D) Chiral alcohol (R)-1-phenylethanol production from acetophenone in engineered E. coli by using methyl viologen (MV) as mediator to achieve EET [55] .…”
Section: Microbial Electrosynthesis (Cathodic Electro-fermentation)mentioning
confidence: 99%
“…Rowe et al found that methyl viologen (MV) shuttled electrons from water-soluble abiotic photosensitizers into S. oneidensis MR-1 to support target reactions including H 2 evolution, CO 2 reduction, succinate and lactate production [ 53 ]. Utesch et al reported a newly developed bioelectrochemical system of C. pasteurianum grown on glycerol by adding artificial mediators neutral red (NR) and brilliant blue (BB) with different electrochemical properties [ 54 ]. The addition of NR leaded to metabolic shifts in BES and increased the n‐butanol yield by as high as 33%, while BB preferred to enhance the formation of 1,3‐propanediol ( Fig.…”
Section: Microbial Electrosynthesis (Cathodic Electro-fermentation)mentioning
confidence: 99%
“…Utesch et al. compared the effects of Brilliant Blue (BB) and NR in both iron‐limiting and iron‐excess conditions on butanol and 1,3‐PDO production during glycerol fermentation with Clostridium pasteurianum [37] . Iron itself was able to act as a mediator under BES conditions.…”
Section: Combining Electrochemical Systems With Living Cellsmentioning
confidence: 99%
“…stirred tank and bubble column). This system has been successfully used for in situ generation of H 2 and O 2 , control of redox potential and recharge of electron mediator for electricity‐aided production of 1,3‐propanediol and n ‐butanolin laboratory scales (0.5 and 2.5 L) . Another design which may be suitable for a rational scale up is an electrochemical bubble column reactor.…”
Section: Scale Up In Electrobiotechnologymentioning
confidence: 99%